Analisis Perbedaan Pengungkapan Corporate Social Responsibility Pada Perusahaan High Profile dan Low Profile (Studi Empiris Perusahaan Manufaktur yang Terdaftar di BEI) - Aida Yulia; Afrianti Afrianti (Jurnal Dinamika Akuntansi dan Bisnis, 2014)
The purpose of this study was to examine the influence of revenue variance regional government budget either simultaneously or partially, toward expenditure variance regional government budget seein in the perspective of agency. The research was conducted at all regions throughout the province Indonesian government. Types of research used in this study is hypothesis testing. The research method used in this study is the method by purposive sampling. The population in this study is all districts across cities in Indonesia. Samples in this study were 56 urban districts that have a budget deficit from 2009 to 2011. The data collection techniques using secondary data from the budget documents that have certain criteria that is done by documentation. Hypothesis testing is done by simple linear regression method. These results of this study indicate that variance revenue budget exists purely partial effect on spending budget exixts purely variance in agency theory perspective.